2021
DOI: 10.3390/molecules26247693
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytochemical Contents, Antioxidant and Antibacterial Activities of Various Solvent Extracts Obtained from ‘Maluma’ Avocado Pulp Powder

Abstract: Although avocado is a superfood rich in phytochemicals with high antioxidant activities, studies on the antibacterial properties of its pulp are limited, except for seed and peel portions. In this study, three types of solvent (acetone, methanol, and diethyl ether) were used to obtain the extracts from “Maluma” avocado pulp powder prepared by infrared drying. The extracts were analyzed for total polyphenols, phytopigments (total chlorophylls and carotenoids), antioxidant activities (ferric-reducing antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…Whereas, the acetone extract (47.5 mg GAEq./mg) showed the lowest antioxidant activity among the studied extracts. Similar high antioxidant activity of ethanolic and methanolic extracts of avocado pulp powder with the highest anti-bacterial activity has been reported recently [ 39 ].…”
Section: Resultssupporting
confidence: 80%
“…Whereas, the acetone extract (47.5 mg GAEq./mg) showed the lowest antioxidant activity among the studied extracts. Similar high antioxidant activity of ethanolic and methanolic extracts of avocado pulp powder with the highest anti-bacterial activity has been reported recently [ 39 ].…”
Section: Resultssupporting
confidence: 80%
“…This could be because the seaweed may contain a high concentration of polar bioactive chemicals soluble in highly polar solvents such as methanol. Methanol has been reported to be more efficient in extracting polyphenols with lower molecular weights [41,42]. These findings suggest that methanol is the most effective solvent for extracting bioactive chemicals from Ulva reticulata.…”
Section: Discussionmentioning
confidence: 87%
“…Methanol extracts of different plant species have been reported to show strong antibacterial activity against a wide range of bacteria since they possess the highest antibacterial and significant antioxidant activities. [29][30] Moreover, it has been indicated in previous studies that sonicationassisted extracts exhibited the best antimicrobial properties. [31][32] Results also showed that the lowest inhibitory effect was recorded with the extract obtained by infusion (extract 7) against E. coli, Mycobacterium, and Pseudomonas.…”
Section: Resultsmentioning
confidence: 99%